Occupational stress as challenge and pressure: Its relationship with personality traits - Escamilla Quintal, Magdalena (Consorcio de Universidades Mexicanas A.C., 2012)
Generally, psychology has focused on pathological stress (Siegel & Schrimshaw, 2000; Peiro, 2008). However, positive psychology emphasizes emotions, attitudes and actions aimed at obtaining happiness and positive workplaces (Simmons & Nelson, 2007). Nevertheless, both perspectives do not oppose each other since –as it has been shown- positive emotions may coexist with negative ones during stressing and adverse circumstances. The aim of this study was to analyze the relationship between appraisal/perception as pressure or challenge stressors and personality traits: optimism, resilience and locus of control. One hundred and seventeen high school and college teachers at Merida, Yucatan, Mexico participated in the study. The findings showed that optimism correlates positively with personal responsibility perceived as challenge, and negatively with workload and balance work/home; resilience correlated positively with relationships at job and locus of control correlated negatively with relationships at job and balance work/home. Findings, contributions and limitations are discussed.